2016
DOI: 10.4111/icu.2016.57.6.408
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral stenting can be a negative predictor for successful outcome following shock wave lithotripsy in patients with ureteral stones

Abstract: PurposeTo evaluate ureteral stenting as a negative predictive factor influencing ureteral stone clearance and to estimate the probability of one-session success in shock wave lithotripsy (SWL) patients with a ureteral stone.Materials and MethodsWe retrospectively reviewed the medical records of 1,651 patients who underwent their first SWL. Among these patients, 680 had a ureteral stone measuring 4–20 mm and were thus eligible for our study. The 57 patients who underwent ureteral stenting during SWL were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Circumstances where stenting can be helpful is for obstructing stones, a large stone in a solitary kidney, obstruction with infection, renal failure and intolerable pain [2] . Routine stenting for ureteral stones has shown to decrease SFR by 15%–22% for stones less than 10 mm [92] , [93] , [94] , and the negative effect may be amplified for larger stones [95] . The role of ureteric stents for renal calculi has not been shown to be of any benefit for renal stone clearance and does not seem to have an obvious impact on the development of steinstrasse [96] , [97] .…”
Section: Strategies To Promote Stone Passagementioning
confidence: 99%
“…Circumstances where stenting can be helpful is for obstructing stones, a large stone in a solitary kidney, obstruction with infection, renal failure and intolerable pain [2] . Routine stenting for ureteral stones has shown to decrease SFR by 15%–22% for stones less than 10 mm [92] , [93] , [94] , and the negative effect may be amplified for larger stones [95] . The role of ureteric stents for renal calculi has not been shown to be of any benefit for renal stone clearance and does not seem to have an obvious impact on the development of steinstrasse [96] , [97] .…”
Section: Strategies To Promote Stone Passagementioning
confidence: 99%
“…[ 4 ] In the EAU guidelines, RIRS and SWL are not recommended as first-line treatments for larger stones in uncomplicated cases, as stone-free rates are less than those with PCNL, and staged procedures have become necessary. [ 5 , 6 ] However, several researchers have reported that RIRS is feasible for stones larger than 2 cm and produces stone-free rates that are similar to those achieved with PCNL. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence and incidence of urolithiasis has been reported to depend on the geographic locations and socioeconomic characteristics of different populations ( 15 ). The incidence of urolithiasis in Korea has progressively increased, in a manner similar to that seen in other developed countries ( 3 16 17 ). A nationwide population-based study reported that the annual incidence of urolithiasis in Korea was 457 per 100,000 population in 2009, which was higher than that of Iran (145.1 per 100,000 population) and Japan (134.0 per 100,000 population), but lower than a range of values (from 0.5% to 1.5%) in western countries ( 3 4 18 ).…”
Section: Discussionmentioning
confidence: 51%